Physico-chemical, sensory, and microbiological quality of raw chicken meat: an exploratory study in the Hisar city of Haryana, India - Bhawana, Indora; Malik, Ashok; Raposo, António; Singh, Shubha; Yadav, Sanjay; Zandonadi, Renata Puppin; Lho, Linda Heejung; Han, Heesup; Thakur, Neha (Frontiers in Nutrition, 2023)
A survey was conducted in Hisar, located in Haryana, India, to assess the quality of raw chicken meat. To ensure comprehensive coverage, healthy broiler chickens were obtained from various meat retail outlets in Hisar city, encompassing the majority of such establishments. Additionally, a sample of control chickens was obtained from the Livestock Farm, College of Veterinary Sciences, Lala Lajpat Rai University of Veterinary and Animal Sciences (LUVAS), Hisar, Haryana, India. The raw chicken meat was grouped into two categories, breast cut and thigh cut. The breast muscles, which include pectoralis major and pectoralis minor, and the thigh muscles, which include the abductor muscles, were chosen as the samples for proximate analysis, which included physico-chemical, sensory, and microbiological analyses of raw chicken meat. The analysis of the raw meat in the laboratory revealed inconsistent variations between the control and retail samples in terms of parameters, such as proximate composition, pH, the water-holding capacity (WHC), thiobarbituric acid (TBA), instrumental color analysis, and sensory evaluation. The moisture content of the control breast sample was significantly higher (p < 0.05) than that of the samples from shops 2, 3, and 5. However, it was statistically similar to that of the samples from shops 1, 4, and 6. The total plate and psychrotrophic counts of the control thigh sample were significantly lower than those of the samples from shops 3, 4, 5, and 6. Among the thigh pH values, the samples from shops 1, 2, 5, and 6 had significantly higher pH values than the control sample. The variations in the various parameters were multifactorial and established the superiority of birds slaughtered under laboratory conditions and grown in university farms compared to the raw chicken meat available in retail outlets in Hisar city.